The Role of Green Supply Chain Activities in Managing Environmental Quality Costs Applied Research in The Gas Filling Company - Khawla Hussein; Noor Fadhil Shahatha (Journal of Madenat Alelem University College, 2020)
The aim of the research is to use green processing activities (green design, green procurement, green manufacturing, green storage, green marketing) to manage environmental quality costs in such a way as to reduce internal and external failure costs by giving importance to prevention and evaluation costs. The conclusions are that the adoption of the Green Processing Series activities leads to the creation of a competitive advantage for the company and the proper management of environmental costs.